A intervenção do provedor de justiça na prevenção e reparação de injustiças dos poderes públicos - Morais, José Domingos de (2013)
This paper focuses on the relevance of the figure of the Ombudsman in Angolan law, as an institution guaranteeing respect for the rights, freedoms and guarantees of citizens towards public authorities. Therefore, this research aims to analyze the role of this body in its intervention to prevent and remedy the injustices of government, having as its mechanism of action recommendations to target organs after submission of complaints by individuals of the actions or omissions of powers public. Thus, among the main obstacles in the intervention of the Ombudsman is the lack of decision making power of its recommendations. The thesis is grounded in research referenced in bibliographical information, looking to make a comparative study of the figure of the Ombudsman in the Angolan relatively few jurisdictions that enshrine this figure in its Constitution. The event aims to highlight the Ombudsman as an organ useful for checking the legality and justice that the law imposes on the Angolan government, in ensuring respect for the rules and principles of law and the system as a mechanism for access to law and justice, which aims to defend the rights, freedoms and guarantees of citizens of the activity of public administration. Focusing on this aspect of the dissertation will address the role of this body for institutions who exercise judicial functions under enshrined in the Constitution of the Republic of Angola, in order to ensure the realization of the democratic state of law. Therefore, intending still sharpen the awareness that, regardless of enjoying power without making claims to this court required the State, the Ombudsman plays a key role in the prevention and remedying of injustices and illegalities of government.